Propagação de maré na baía do Marajó e seus principais tributários - SANTOS, Arthur Souza dos (2019)
The wide hydrographic network of Amazon region, approaching from its mouth assumes oceanographic features and gives rise to an estuary ecosystem. The tide is the variation of sea levels caused by astronomical forcings, its propagation in an estuary mainly results its oscillatory motion in the river mouth and runoff. Under that natural effect is the Marajó bay, an estuary formed mainly by water from the Pará and Tocantins rivers and Guajará bay. Inside that context, the objective was to determinate the pattern of tide propagation in the Marajó bay and its major tributaries, identifying its harmonics and phases differences between distinct points in the estuary. For this analysis, tidal data were collected for two years at a station located in Val-de-Cães Naval Base in Belém, as well as a pressure sensors network installed on both sides of the Marajó bay and where Pará and Tocantins rivers meet each other. The study was conducted between 2012 and 2013. The analyzes were performed separately in each portion of the estuary. The region shows a decrease in the amplitude of the tide toward the downstream, showing regime of meso to macrotidal, the central portion presented amplitudes of up to 3.5 meters in the spring tide and the delay at the high tide between the outer section and the inner section was about four hours.